Femtosecond laser synthesis of nitrogen-doped luminescent carbon dots from acetonitrile. (April 2021) - Astafiev, Artyom A.; Shakhov, Aleksander M.; Kritchenkov, Andreii S.; Khrustalev, Victor N.; Shepel, Denis V.; Nadtochenko, Victor A.; Tskhovrebov, Alexander G.
Abstract: Carbon dots (CDs) is a novel promising class of nanomaterials with unique properties. Most of synthetic methods to obtain CDs employ hydrothermal synthesis, breaking down larger carbon materials by laser irradiation, arc discharge, ultrasonication or electrolysis. Here we describe a conceptually new bottom-up approach to nitrogen-rich carbonaceous nanoparticles via high intensity femtosecond laser irradiation of neat acetonitrile where the latter serves a source of the doping N atoms. Selected photophysical properties of the new material and mechanism of the photoluminescence (PL) are discussed. Highlights: Conceptually new approach to the synthesis of nitrogen-rich carbonaceous nanoparticles. Neat acetonitrile as a source of the doping N atoms. New carbon nanoparticles exhibit unique physical characteristics distinctive from those of obtained via traditional approaches. Photophysical studies.